2000
DOI: 10.1046/j.1460-9568.2000.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience‐dependent plasticity of visual acuity in rats

Abstract: Rats have become a popular model for investigating the mechanisms underlying ocular dominance plasticity; however, no quantitative assessment of the effects of visual deprivation on behavioural acuity has been reported in this species. We measured the spatial acuity of monocularly and binocularly deprived rats with a visual discrimination task. The average spatial acuity of normal rats and rats deprived of vision after postnatal day 40 was approximately 1 cycle/degree. Monocular deprivation up to postnatal day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 44 publications
4
49
0
Order By: Relevance
“…1E). Visual acuity of the other eye was within the normal acuity values estimated with VEPs or behaviorally in the rat (11,19). Thus the amblyopic effects of MD are not rescued by 1 week of RS.…”
Section: Lack Of Spontaneous Recovery Of Visual Acuity Of the Long-term-supporting
confidence: 51%
See 1 more Smart Citation
“…1E). Visual acuity of the other eye was within the normal acuity values estimated with VEPs or behaviorally in the rat (11,19). Thus the amblyopic effects of MD are not rescued by 1 week of RS.…”
Section: Lack Of Spontaneous Recovery Of Visual Acuity Of the Long-term-supporting
confidence: 51%
“…Recovery from the amblyopic effect of MD is also progressively less efficient during development. In the adult, visual acuity shows small recoveries even if its final level continues to be pathologically low (10,11). Similarly, a limited recovery of visual acuity can also be observed in adult amblyopic patients in particular conditions (1), although visual acuity remains largely abnormal.…”
mentioning
confidence: 99%
“…We have tested the visual acuity of pigmented acallosal mice [29], however, and found that their acuity of about 0.5 c/d was not significantly lower than that of control mice (unpublished observations). In addition, lesions of striate cortex [8], and monocular deprivation in LongEvans rats throughout early life [19], reduce visual acuity by just 30%, not the 50% deficit that characterizes the albino strains in this study. It is possible that the anomalies caused by albinism produce a form of longterm deprivation for the visual system, which results in experience dependent abnormalities in both central and retinal visual processing, and this may produce a massive deprivation-induced deficit in acuity.…”
Section: Albino Rat Strains With Acuity Near 05 C/dmentioning
confidence: 48%
“…We have also reported that visual deprivation in rats during a physiologically-defined critical period early in life [26] results in significantly reduced visual acuity [19]. This suggests that mature visual function in the rat, like that of other mammals [6], is dependent on the nature of visual experience during development.…”
Section: Introductionmentioning
confidence: 78%
“…62,63 Similarly, in animal models, the classic hallmarks of amblyopia are a permanent loss of VA in the affected eye and a pronounced OD shift of visual cortical neurons in favour of the normal eye. [64][65][66][67][68] Traditional amblyopia therapy consists of patching Figure 2 (a) Enriched pups experience higher levels of maternal care compared with standard-reared pups. (A1) The frequency of 'pups alone in the nest' recordings during the first 10 days postpartum in non-environmental enrichment (EE) (white) and EE (black) animals.…”
Section: Rejuvenating the Adult Brainmentioning
confidence: 99%